2012
DOI: 10.1186/1472-6874-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Rates of IUCD discontinuation and its associated factors among the clients of a social franchising network in Pakistan

Abstract: BackgroundModern Intrauterine contraceptive device (IUCD) is very safe, highly effective reversible and inexpensive family planning method which offers 5-10 years of protection against pregnancy. The contraceptive use in Pakistan has been merely 30% for over a decade with IUCD being the least used method. Higher discontinuation rates are documented in developing countries; however no such data is available for Pakistan. Marie Stopes Society (MSS) established a social franchise outlets network branded as 'SURAJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
81
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 10 publications
13
81
2
Order By: Relevance
“…62.5 % of the females using contraception in any form discontinued IUCD use as against 83 % among those who had not used the contraception in the past, indicating the motivated women's desire to have a safe and long-lasting contraceptive method (Table 3). This was in accordance with the results obtained in Pakistan by Azmat et al [8].…”
Section: Resultssupporting
confidence: 94%
“…62.5 % of the females using contraception in any form discontinued IUCD use as against 83 % among those who had not used the contraception in the past, indicating the motivated women's desire to have a safe and long-lasting contraceptive method (Table 3). This was in accordance with the results obtained in Pakistan by Azmat et al [8].…”
Section: Resultssupporting
confidence: 94%
“…[8] 66.66% of the females using contraception in any form discontinued IUCD as against 85.08% among those who had not used the contraception in any past. This is in accordance with the results obtained in Pakistan by Azmat et al [9] The result also corroborated well with the study by Sharma Megha et al [4] It indicates that the motivated women desire to have a safe and long-lasting contraceptive method. In our study, type of insertion has no significant effect as discontinuation rate as in accordance with study by Sharma Megha et al [4] CONCLUSION The average duration of IUD use in a majority of the females was about 36 months, thereby fulfilling its objective of spacing between the children as laid down by WHO (2 years spacing between pregnancies).…”
Section: Discussionsupporting
confidence: 83%
“…Their role in improving the maternal health status of the country has been well appreciated by the international community as well. 12 Similarly, this study also highlighted that the FCHVs as the source of information has a positive significant association with IUCD use. This association might have been attributed due to the fact that the Government of Nepal has provided incentive for FCHVs for tracking the client to increase the use of IUCD.…”
Section: Discussionmentioning
confidence: 65%
“…[4][5][6][7] Several studies done in other countries revealed that factors like education, place of residence, culture, religion, literacy, occupation, income, reproductive intention, spousal communication and service related factors influence women's behavior to use IUCD. [8][9][10][11][12][13][14][15][16] Studies had shown that the reason for non-use is the fear of side effects. 17,18 However, studies from Nepal did not provide adequate reliable information about the factors for use and non-use of the device.…”
Section: Introductionmentioning
confidence: 99%